Penerapan Metode Respiration Training Terhadap Klien Disfonia Umur 74 Tahun : Studi Kasus Tunggal - nining lestari; Salsabila Khoirunnisa (Jurnal Terapi Wicara, 2025)
Background: Voice problems caused by allergic rhinitis and poor lifestyle choices, such as those experienced by active smokers. A hoarse and weak voice can impact a person's daily activities. Speech therapists provide voice therapy aimed at optimising vocal function in order to improve quality of life. Objective: This study aims to obtain an overview of changes in voice improvement after treatment. Method: Using a single subject quasi-experimental research method, with an A1-B-A2 design, where A1 is the pretest/before intervention, B is the intervention, and A2 is the posttest/after intervention with 10 Respiration Training sessions. The subject of this study was a 74-year-old male who experienced hoarseness with a history of allergic rhinitis, frequently cleared his throat, and was an active smoker. Voice quality measurements were conducted using auditory, acoustic, and aerodynamic perception before therapy. Maximum phonation time measurements were also conducted before and after therapy. Results: After 10 interventions using the Respiration Training method, there was an improvement in duration ability by prolonging the vowels. Conclusion: Respiration Training plays a role in helping clients regulate airflow and subglottic pressure, thereby prolonging maximum phonation time and improving voice production efficiency. This method can also be combined with various other phonation techniques to strengthen the voice and achieve a more optimal phonation process.